Design and fabrication power window apparatus (bowden cable type) - Ahmad Kamil, Miskam (2007)
The main purpose of this Power window apparatus project is to train final year student for hands on experience and to work by themself. The study of manufacturing is very important in order to ensure that student understand on what are the needs to do in this project. This project is about designing and fabricating the Power Window Apparatus for experimental use to help the students in a Automotive course for easy understanding the basic system of power window and how it works. This project involves the process of designing the test panel by considering the shape and also the advantages for student to use in their learning process. After the design has been completed, it was transformed to the real product by fabricating process where the design is used for guideline. This project also required analysis to test the power window operation failure factor. Numerous methods and process involve in this project for instance joining using welding process. After all the process had been done, this power window apparatus help us to understand the fabrication and designing process that involved in this project.